PEMBUATAN KIT SEDERHANA KALORIMETER DARI BAHAN BEKAS BAGI GURU IPA FISIKA - Lydia Rohmawati; Woro Setyarsih; Nugrahani Primary Putri (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2019)
Students are actively demanded such as observing, asking questions, collecting data, associating, and communicating mainly in science learning. However, laboratory facilities in South Surabaya Middle School are known incomplete and some do not even have a laboratory, so as the teacher gives the material using the lecture method. One of the science materials is thermodynamics, especially with regard to calorimeter devices, whose application is about Black Principle. The calorimeter equipment on the market is very expensive, so it is necessary to conduct training and assistance on making simple calorimeter tools bywaste material. The training carried out on the Surabaya South Science MGMP teachers included making calorimeters by used materials, testing tools by practical training, and giving questionnaires in the form of responses and suggestions related to training activities. The results obtained from this activity included the knowledge and skills of the teachers in making simple calorimeter tools of waste material, and positive attitudes from the teachers to apply the tool as a medium of learning in the classroom.